2017
DOI: 10.1101/229971
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The rust fungus Melampsora larici-populina expresses a conserved genetic program and distinct sets of secreted protein genes during infection of its two host plants, larch and poplar

Abstract: SummaryMechanims required for broad spectrum or specific host colonization of plant parasites are poorly understood. As a perfect illustration, heteroecious rust fungi require two alternate host plants to complete their life cycle. Melampsora larici-populina infects two taxonomically unrelated plants, larch on which sexual reproduction is achieved and poplar on which clonal multiplication occurs leading to severe epidemics in plantations. High-depth RNA sequencing was applied to three key developmental stages … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
1
2
0
Order By: Relevance
“…483 The distribution of expressed unigenes of the apple rust fungus in functional KOG 484 categories shows similar overall patterns in spermogonia and in aecia in apple tree, as 485 well as in telia on the alternate host juniper. The same conclusion was reached for M. 486 larici-populina on the two hosts, poplar and larch (Lorrain et al 2018). These 487 transcriptomes studies suggest the expression of conserved molecular mechanisms in 488 rust fungi during infection of different hosts and at different sporulation stages.…”
Section: Introductionsupporting
confidence: 54%
“…483 The distribution of expressed unigenes of the apple rust fungus in functional KOG 484 categories shows similar overall patterns in spermogonia and in aecia in apple tree, as 485 well as in telia on the alternate host juniper. The same conclusion was reached for M. 486 larici-populina on the two hosts, poplar and larch (Lorrain et al 2018). These 487 transcriptomes studies suggest the expression of conserved molecular mechanisms in 488 rust fungi during infection of different hosts and at different sporulation stages.…”
Section: Introductionsupporting
confidence: 54%
“…In the case of the rust fungi of the class Pucciniales, the hosts often belong to phylogenetically distant groups, such as angiosperms and gymnosperms or monocots and dicots (Aime et al, 2018). The host switching within the life cycle in these cases is likely enabled by a strong separation of gene regulation in monokaryotic and dikaryotic hyphae (Lorrain et al, 2018), which might be enabled by stagespecific transcription factors that can only be activated or deactivated in the presence or absence of a second nucleus in a hyphal compartment. By switching hosts concomitantly, the possibility of variation beyond optimal interaction is providedsub-optimal performance on one of the two hosts may be outweighed by more successful performance on the other.…”
Section: Reviewmentioning
confidence: 99%
“…Very little information is available about infection mechanisms of alternate hosts and sexual stages. To date, only a handful of studies have considered gene expression on the alternate host and they have revealed concomitant expression of sets of candidate effectors in both hosts as well as in each host individually Liu et al, 2015;Cuomo et al, 2017;Lorrain et al, 2018a). This type of approach is particularly helpful for narrowing down the list of effectors related to the main host where disease causes the most significant damage.…”
Section: Reviewmentioning
confidence: 99%